(531) السمات الاساسيه للقطاع الزراعى في العراق The basic characteristics of the agricultural sector in Iraq - سعد طه علام (معهد التخطيط القومي, 2026)
يستعرض هذا الملف السمات الأساسية للقطاع الزراعي في العراق، موضحاً أنه يمثل ركيزة أساسية للاقتصاد القومي ومجالاً رئيسياً للتوظيف، حيث تبلغ المساحة القابلة للزراعة فيه نحو 48 مليون دونم. وتعتمد أساليب الإنتاج فيه على منطقتين رئيستين: المنطقة الشمالية التي تعتمد على الأمطار، والمنطقتان الوسطى والجنوبية اللتان تعتمدان على مياه نهري دجلة والفرات. ويتنوع الإنتاج الزراعي بين المحاصيل الحقلية كالقمح والشعير، والمحاصيل الصناعية كالقطن والتبغ، بالإضافة إلى ثروة حيوانية هامة تتصدرها الأغنام والماعز، مع تميز العراق بامتلاك نحو 40% من عدد النخيل في العالم، مما يجعله من كبار منتجي التمور عالمياً. وعلى الرغم من هذه الإمكانات، يواجه القطاع الزراعي تحديات هيكلية وطبيعية تحد من كفاءته، ومن أبرزها مشكلة ملوحة التربة، وتذبذب كميات المياه المتاحة، والاعتماد الكبير على منابع مائية تقع خارج الحدود السياسية للدولة، مما يتطلب تنسيقاً دائماً مع دول الجوار. كما تظهر البيانات تراجعاً في المساهمة النسبية للزراعة في الناتج المحلي الإجمالي لصالح قطاع النفط، إلى جانب انخفاض إنتاجية الدونم الواحد مقارنة بدول أخرى. ولذلك، تهدف خطط التنمية الاقتصادية في العراق إلى تعزيز هذا القطاع عبر تحسين أساليب الري، ونشر الجمعيات التعاونية، وتطوير الخدمات البيطرية لتقليل الفوارق المعيشية بين سكان الريف والحضر. This report examines the key features of the agricultural sector in Iraq, highlighting its crucial role as a pillar of the national economy and a major source of employment, with approximately 48 million dunams of arable land. Production methods are concentrated in two main regions: the rain-fed northern region and the central and southern regions, which rely on the Tigris and Euphrates rivers. Agricultural production is diverse, encompassing field crops such as wheat and barley, industrial crops like cotton and tobacco, and a significant livestock sector, primarily sheep and goats. Iraq also boasts approximately 40% of the world's date palms, making it a major global date producer. Despite these potentials, the agricultural sector faces structural and natural challenges that limit its efficiency. These include soil salinity, fluctuating water availability, and heavy reliance on water sources located outside the country's borders, necessitating ongoing coordination with neighboring countries. Data also reveals a decline in agriculture's relative contribution to the GDP, with the oil sector gaining ground, and lower yields per dunam compared to other countries. Therefore, economic development plans in Iraq aim to strengthen this sector by improving irrigation methods, spreading cooperative societies, and developing veterinary services to reduce living disparities between rural and urban populations.